2004
DOI: 10.1093/geronb/59.2.s68
|View full text |Cite
|
Sign up to set email alerts
|

Do Impaired Older Persons With Health Care Needs Occupy U.S. Assisted Living Facilities? An Analysis of Six National Studies

Abstract: ALFs are currently serving older residents who require less nursing care and who are less functionally and cognitively impaired than those found in nursing homes. The more restrictive admitting and discharge criteria of a substantial share of ALFs guarantee their less frail occupant profile. This is, however, an extraordinarily diverse shelter and care alternative, and very frail older persons with serious chronic health problems can be found in ALFs. Average duration of stays may be as long as 3 years. Resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 8 publications
1
70
0
Order By: Relevance
“…In addition to different populations, low response rates and response bias can further result in misleading figures. Hawes and colleagues' sample included 1,251 residences in 34 states (response rate = 81%), and the National Investment Conference studied 178 residences in 47 states (response rate = 54%); although less than optimal, these rates are comparable to those of other work in the field (Golant, 2004).…”
Section: The Evolution Of Al and Al Typologiesmentioning
confidence: 86%
“…In addition to different populations, low response rates and response bias can further result in misleading figures. Hawes and colleagues' sample included 1,251 residences in 34 states (response rate = 81%), and the National Investment Conference studied 178 residences in 47 states (response rate = 54%); although less than optimal, these rates are comparable to those of other work in the field (Golant, 2004).…”
Section: The Evolution Of Al and Al Typologiesmentioning
confidence: 86%
“…Nursing homes are considered health care institutions and are regulated by federal (i.e., U.S. Department of Health and Human Services Centers for Medicare and Medicaid Services [CMS]) and state (i.e., Department of Health) authorities. In contrast, oversight of community-based assisted living facilities is state regulated and personal care assistance is offered as a supplement to private housing and hospitality services for residents who are generally more physically and mentally healthy than their nursing home counterparts (Golant 2004;Hyer et al 2006;Laditka et al 2009). …”
mentioning
confidence: 99%
“…Based on his review of six national studies, Golant (2004) concluded that assisted living residences were more likely to accept frail older persons when these people had less serious cognitive impairments and when they did not require ongoing supervision (e.g., did not wander; or did not have memory, judgment, or behavioral problems). He also indicated that less than 50% of the assisted living residences would accept older persons if they had moderate to severe cognitive impairments.…”
Section: Move-in/move-out Criteriamentioning
confidence: 99%